Pressure Overload in Mice With Haploinsufficiency of Striated Preferentially Expressed Gene Leads to Decompensated Heart Failure - Shu, Chang; Huang, He; Xu, Ying; Rota, Marcello; Sorrentino, Andrea; Peng, Yuan; Padera, Robert F.; Huntoon, Virginia; Agrawal, Pankaj B.; Liu, Xiaoli; Perrella, Mark A. (Frontiers in Physiology, 2018)
Striated preferentially expressed gene (Speg) is a member of the myosin light chain kinase family of proteins. Constitutive Speg deficient (Speg–/–) mice develop a dilated cardiomyopathy, and the majority of these mice die in utero or shortly after birth. In the present study we assessed the importance of Speg in adult mice. Speg–/– mice that survived to adulthood, or adult striated muscle-specific Speg knockout mice (Speg-KO), demonstrated cardiac dysfunction and evidence of increased left ventricular (LV) internal diameter and heart to body weight ratio. To determine whether heterozygosity of Speg interferes with the response of the heart to pathophysiologic stress, Speg+/– mice were exposed to pressure overload induced by transverse aortic constriction (TAC). At baseline, Speg+/+ and Speg+/– hearts showed no difference in cardiac function. However, four weeks after TAC, Speg+/– mice had a marked reduction in LV function. This defect was associated with an increase in LV internal diameter and enhanced heart weight to body weight ratio, compared with Speg+/+ mice after TAC. The response of Speg+/– mice to pressure overload also included increased fibrotic deposition in the myocardium, disruption of transverse tubules, and attenuation in cell contractility, compared with Speg+/+ mice. Taken together, these data demonstrate that Speg is necessary for normal cardiac function and is involved in the complex adaptation of the heart in response to TAC. Haploinsufficiency of Speg results in decompensated heart failure when exposed to pressure overload.